Christian Confession of Faith, Then and Now - Daniel Trihandarkha (Sekolah Tinggi Teologi Jemaat Kristus Indonesia, Salatiga, 2021)
Confession of faith is part of the tradition in the ecclesial life of believers. We now know The Apostle Creeds which are predominately used in Protestant Church in Indonesia has gone through long stories and journey until it reaches what we have now in Indonesian language. Confession of faith is slightly different because they were made in the different times and different challenges compared with Apostle Creed. This writing will explore the foundational understanding of why confession of faith is necessary in the time of reformation only-the reason will be explained later. How it was and how it is now in the life of believers? We will see the biblical basis, and how it influenced the formulation of the Confession of Faith. Finally we will see the ever present relevance for all of us now.